A regional model for monsoon prediction (MAUSAM, 1990)
A regional six-level primitive equation model has been integrated up to 48 hrs using input of 13 synoptic analyses to evaluate the forecast potential of the model for monsoon prediction. The dominant synoptic features in the input analyses are the monsoon depressions. The predicted movement and phase speed of cy-clonic circulations, the low level jet's strength and position, the simulation of cross-equatorial flow and rainfall rates are examined.